Teaching butterfly using mirrors and fins - Magg, B. (American Swimming Magazine, 1998)
On effective ways to teach the butterfly stroke mechanics to experienced and new swimmers (experiences). With ther new swimmers, especially the young, the author has found that starting with fins is a great help. He describes possible drills. For the more experienced swimmers they use two mirrors and a Simuswim 2000 bench to ensure correct technique. Author describes how it works.